Structure of the streptococcal endopeptidase IdeS, a cysteine proteinase with strict specificity for IgG - Wenig, Katja (National Academy of Sciences, 2004)
Pathogenic bacteria have developed complex and diverse virulence mechanisms that weaken or disable the host immune defense system. IdeS (IgG-degrading enzyme of Streptococcus pyogenes) is a secreted cysteine endopeptidase from the human pathogen S. pyogenes with an extraordinarily high degree of substrate specificity, catalyzing a single proteolytic cleavage at the lower hinge of human IgG. This proteolytic degradation promotes inhibition of opsonophagocytosis and interferes with the killing of group A Streptococcus. We have determined the crystal structure of the catalytically inactive mutant IdeS-C94S by x-ray crystallography at 1.9-Å resolution. Despite negligible sequence homology to known proteinases, the core of the structure resembles the canonical papain fold although with major insertions and a distinct substrate-binding site. Therefore IdeS belongs to a unique family within the CA clan of cysteine proteinases. Based on analogy with inhibitor complexes of papain-like proteinases, we propose a model for substrate binding by IdeS.